Analysis of exploration and exploitation in evolutionary algorithms by ancestry trees. (1st January 2011) - Črepinšek, Matej; Mernik, Marjan; Liu, Shih-HsiLiu
This paper introduces an ancestry tree-based approach for exploration and exploitation analysis. The approach introduces a data structure to record the evolution history of a population and a number of exploration and exploitation metrics. Such an approach not only provides insight of how and when the exploration and exploitation influence an evolution process, but also how the genetic structure of an individual is affected. It can be used to better understand inner working of an evolutionary algorithm or in evolutionary algorithm designing phase to develop suitable variation operators with good balance between exploration and exploitation. The approach is applied to the multi-objective 0/1 knapsack problem.